2020
DOI: 10.1161/hypertensionaha.118.12595
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 (Toll-Like Receptor 4) Mediates the Development of Intracranial Aneurysm Rupture

Abstract: Inflammation is emerging as a critical factor in the pathophysiology of intracranial aneurysm. TLR4 (toll-like receptor 4) contributes not only to the innate immune responses but also to the inflammatory processes associated with vascular disease. Therefore, we examined the contribution of the TLR4 pathway to the development of the rupture of intracranial aneurysm. We used a mouse model of intracranial aneurysm. TLR4 inhibition significantly reduced the development of aneurysmal rupture. In addition, the ruptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Inflammation and immune cell infiltration, including macrophages, mast cells ( Furukawa et al, 2020 ), and monocytes, play important roles in the formation and rupture of IAs. A previous study confirmed that inflammation-accelerated Toll-like receptor 4 (TLR4) pathway in aneurysmal walls promoted the development of IA rupture ( Mitsui et al, 2020 ). Similarly, Kanematsu et al (2011) reported that the infiltration and polarization of macrophages were closely related to the rupture of IAs.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Inflammation and immune cell infiltration, including macrophages, mast cells ( Furukawa et al, 2020 ), and monocytes, play important roles in the formation and rupture of IAs. A previous study confirmed that inflammation-accelerated Toll-like receptor 4 (TLR4) pathway in aneurysmal walls promoted the development of IA rupture ( Mitsui et al, 2020 ). Similarly, Kanematsu et al (2011) reported that the infiltration and polarization of macrophages were closely related to the rupture of IAs.…”
Section: Introductionmentioning
confidence: 68%
“…Higher TNF-α expression is associated with increased expression of intracellular calcium ions (Ca 2+ ) and intracellular calcium release channels ( Jayaraman et al, 2008 ), which are related to the NF-κB signaling pathway and TLR signaling pathway. Moreover, the TLR4 pathway has been found to promote the development of IA rupture by accelerating inflammation in IA walls ( Mitsui et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The normalization of blood pressure in a mice model with aneurysm formation significantly reduced the risk of aneurysmal rupture [ 7 ]. Beyond mechanical stress, activation of the local renin-angiotensin system and toll-like receptor 4 pathway by systemic hypertension can induce vascular inflammation and remodeling, contributing to aneurysm rupture [ 35 ]. Increased activity and imbalances of the metalloproteinase/tissue inhibitors of metalloproteinase system in hypertensive patients predisposes them to cerebral aneurysm formation and growth [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the molecular aspects of macrophage polarization, it has already been shown that toll-like receptor 4 (TLR4) compels macrophages skewedly toward the M1 phenotype in intracranial aneurysms [ 32 , 33 , 34 ]. The signaling cascade via the myeloid differentiation primary response gene 88 (MyD88) leads to the activation of inhibitor kappa B kinase β (IKK β ), which in turn triggers the phosphorylation and successive degradation of inhibitor kappa B (I κ B).…”
Section: Birth By Fire—are Microglia Responsible For Intracranial Anementioning
confidence: 99%